DMS-informed secondary structure modeling of Epstein–Barr Virus LMP-1 pre-mRNA defines novel elements spanning introns - Taylor O. Eich; Evelyn C. Coppenbarger; Abdelraouf O. Dapour; Walter N. Moss (PLoS ONE, 2026)
The Epstein–Barr virus (EBV) infects over 95% of adults, establishing lifelong latency and contributing to the development of various malignancies, including Burkitt lymphoma and nasopharyngeal carcinoma. However, the RNA structures regulating the splicing of the critical EBV gene, latent membrane protein 1 ( LMP1 ), remain uncharacterized. To identify these regulatory elements, we applied spliceosome inhibition with RNA probing and sequencing (SIRP-seq) to the BJAB-B1 cell line. By utilizing the spliceosome inhibitor pladienolide B, we enriched pre-mRNA species, enabling the detection of structural features within both the full-length pre-mRNA ( LMP1-FL ) and an alternatively spliced isoform retaining intron 2 ( LMP1-AS ). The resulting chemical probing datasets informed the RNA folding algorithms RNAfold and ScanFold to generate the first high-resolution secondary structure models for the LMP1 pre-mRNA, encompassing both exonic and intronic regions. Our results identify 11 novel, thermodynamically stable RNA structures, with several key elements positioned near splice junctions. Notably, three structures (Structures 8, 9, and 10) were identified near the 3′ splice site of intron 2, appearing in alternative conformations that may influence splicing accessibility. Furthermore, these structures map to regions containing disease-relevant mutations associated with patient survival in Burkitt lymphoma. This structural framework provides new insights into how LMP1 splicing may be regulated by RNA structure and identifies potential novel therapeutic targets for mitigating EBV-associated diseases.